The Power of Evidence of Witness Testimony in the Trial Process of Criminal Molestery Cases - Mukhali, Mukhali; Sudarmaji, Aji (UNISSULA Semarang, 2024)
The purpose of this research is to determine the strength of the evidence of witness testimony in the trial of a criminal act of indecency. To determine the strength of providing legal protection for witnesses in the trial of a criminal act of indecency. The method used by the researcher is normative legal approach & the specifications in this study include descriptive analysis. The sources and types of secondary data were obtained from literature studies. Based on the results of the study, the evidentiary power of witness statements in a trial of a criminal act of indecency depends on several factors, including: conformity with other evidence: The witness's statement must be consistent with other valid evidence. Conformity with the statements of other witnesses: The witness's statement must be consistent with the statements of other witnesses. The witness's reasons for giving a statement: The judge considers the witness's reasons for giving a particular statement. The witness's lifestyle and morality: The judge considers the witness's lifestyle and morality. The witness's obligation to take an oath: The witness is required to take an oath or promise before giving a statement in court. The Power to Provide Legal Protection for Witnesses in Trials of Criminal Acts of Indecency has not been implemented optimally, this is because there are still children's rights that have not been obtained by children who are victims of criminal acts of indecency, namely the right to receive rehabilitation, rehabilitation both psychologically, physically and spiritually, even though this is regulated in the provisions of the Child Criminal Justice System Law, namely in Article 90 paragraph (1) which states that in addition to the rights that have been regulated in the provisions of laws and regulations as referred to in Article 89, Child Victims and Child Witnesses have the right to medical rehabilitation and social rehabilitation efforts, both within and outside the institution. However, this right is not obtained by child victims of criminal acts of indecency.